Management of Islamic Finance : Principle, Practice, and Performance. - Hassan, M. Kabir (International Finance Review Ser., 2018)
In this issue, we have presented issues relevant to the most recent debate on the performance, practices, and principles of the Islamic finance industry as a whole, covering eleven distinct issues.